2019
DOI: 10.1021/acs.jnatprod.8b00507
|View full text |Cite
|
Sign up to set email alerts
|

Jatrophane Diterpenoids from Euphorbia glomerulans

Abstract: In a phytochemical investigation of the whole plant of Euphorbia glomerulans, 17 new (1−17) and five known jatrophane diterpenoids (18−22) were identified. The X-ray crystallographic data of compounds 1, 4, and 21 permitted the definition of the absolute configurations of these compounds. The cytotoxicity and multidrug resistance reversal activities of the 17 new compounds were evaluated on multidrug-resistant MCF-7/ADR cells overexpressing P-glycoprotein. Several compounds showed different chemoreversal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…The presence of an isobutanoyloxy moiety at C-8 rather than at C-7 had a positive effect on the modulation of drug accumulation in the MCF-7/ADR cells by comparing the substituents and RF values of 314, 315, and 316. Furthermore, with the comparison of the biological results of 307, 309, and 311 to those of 308, 310, and 318, it was demonstrated that favorable following trend in activity at C-8 is: benzoyloxy group [ H & hydroxy group (Hasan et al 2019). Remy and Litaudon (2019) have published a review on anti-CHIKV activity of eighty diterpenoids covering the years 2011 to 2019.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…The presence of an isobutanoyloxy moiety at C-8 rather than at C-7 had a positive effect on the modulation of drug accumulation in the MCF-7/ADR cells by comparing the substituents and RF values of 314, 315, and 316. Furthermore, with the comparison of the biological results of 307, 309, and 311 to those of 308, 310, and 318, it was demonstrated that favorable following trend in activity at C-8 is: benzoyloxy group [ H & hydroxy group (Hasan et al 2019). Remy and Litaudon (2019) have published a review on anti-CHIKV activity of eighty diterpenoids covering the years 2011 to 2019.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…In addition to these signals, the 13 C NMR spectrum displayed four methyls ( δ C 20.7, 23.1, 24.0 and 25.2), one sp 3 methylene ( δ C 52.3), one sp 2 methylene ( δ C 114.2), five sp 3 methines ( δ C 42.8, 47.7, 65.2, 72.7 and 81.0), two sp 2 methines ( δ C 133.1 and 136.1), three sp 3 quaternary carbons ( δ C 49.6, 79.1 and 85.2) and three sp 2 quaternary carbons ( δ C 138.0, 204.9 and 213.2). These signals account for 19 carbons, indicating the absence of one carbon signal that may be attributed to conformational exchange of the jatrophane type diterpenoid molecule [ 17 , 18 ]. The spectroscopic data of 1 was similar to (2 S *,3 S *,4 R *,5 R *,7 S *,8 R *,13 S *,15 R *)-5,7,8-triacetoxy-3-benzoyloxy-15-hydroxyjatropha-6(17),11 E -diene-9,14-dione ( 5 ) [ 17 ] except for the presence of signals responsible for an hydroxy group ( δ H 2.33) and an additional oxygenated quaternary carbon ( δ C 79.1), the absence of the proton signal at C-2.…”
Section: Resultsmentioning
confidence: 99%
“…The newly reported diterpenoids structures led to new information about their biological activities and their biogenesis in plants. Plants newly investigated within this time frame were E. kopetdaghi [ 25 ], E. sanctae-catharinae [ 26 ], E. gaditana [ 27 ], E. saudiarabica [ 28 ], and E. glomerulans [ 29 ].…”
Section: Occurrence Of Euphorbia Diterpenesmentioning
confidence: 99%
“…The cytotoxic evaluation of jatrophane diterpenoids isolated from the acetone extracts of E. glomerulans on multidrug-resistant breast cancer cells (MCF-7/ADR) was found to overexpress the P-glycoprotein (P-gp) with varying chemoreversal abilities and with reduced cytotoxicity activity. Euphoglomeruphane K ( 233 ) and L ( 234 ) showed better MDR reversal activity, with IC 50 values of 5.00 μM and 5.10 μM, respectively, compared to verapamil, the positive control, with IC 50 value of 4.70 μM [ 29 ].…”
Section: Pharmacological Activities and Structure–activity Relationship (Sar)mentioning
confidence: 99%
See 1 more Smart Citation